Pengembangan Media Ular Tangga Edukatif pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN Panancangan 5 - Brilianti Ismaila; Tifani Maulidah; Deva Radia Saputri; Ana Nurhasanah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This study aims to develop educational Snakes and Ladders media to increase student participation and engagement in Pancasila Education learning for fourth-grade students at SDN Panancangan 5. This study uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The needs analysis shows that low student participation is caused by the use of monotonous and one-way learning media. The developed product was validated by material experts and media experts. The first material validation obtained 95.29% and increased to 98.82% after revision, while media validation increased significantly from 60% to 95.38% after design improvements. The average expert validation score reached 87.37%, categorized as